A review on thermal conversion of plant oil (edible and inedible) into green fuel using carbon-based nanocatalyst - Alsultan, Abdulkareem Ghassan; Mijan, Nurul Asikin; Lee, Hwei Voon; Rashid, Umer; Islam, Aminul; Yap, Taufiq Yun Hin (MDPI, 2019)
Renewable diesels (e.g., biodiesel and green diesel) have emerged as a sustainable alternative to petrodiesel as a means of meeting the growing demand for fuel without damaging the environment. Although renewable diesels are composed of different chemical compositions to petrodiesel, they provide similar fuel characteristics as petrodiesel. The present articles focused on various type of green diesel, where the properties and its performance are discussed in detail. Green diesels offer multiple benefits over petrodiesel in terms of biodegradability, environmental protection and low toxicity. Additional, this paper described various types of process for green diesels production such as deoxygenation, hydrodeoxygenation, and pyrolysis. Among the synthesis process, the most effective and economical route to produce green diesel is through deoxygenation (DO). This study also emphasizes the use of a carbon-based catalyst for the DO reaction. The carbon-based catalyst renders several advantageous in term of highly resistance toward coke formation, greater catalyst stability, and product selectively, where the DO process occur via carbon–oxygen cleavage of fatty acid chain yielding diesel-like hydrocarbons. Due to this reason, various methods for synthesizing effective carbon-based catalysts for the DO reaction are further reviewed. Coke affinity over carbon-base catalyst during DO process is further discussed in the present study. Besides, DO operating condition toward optimum yield of hydrocarbons and recent progress in DO of realistic oil for production of diesel-like hydrocarbons are also discussed herein.